Randomized-controlled trial of response inhibition training for individuals with PTSD and impaired response inhibition. (August 2021) - Echiverri-Cohen, Aileen; Spierer, Lucas; Perez, Marcelina; Kulon, Melissa; Ellis, Montana Daunbi; Craske, Michelle
Abstract: Deficits in response inhibition, defined as an inability to stop a behavior that is no longer relevant, are characteristic of posttraumatic stress disorder (PTSD). Given that impaired response inhibition is associated with worse symptom recovery and accumulating evidence pointing to the effectiveness of cognitive control trainings in reducing PTSD symptoms, individuals with moderate to severe PTSD total severity (Posttraumatic Diagnostic Scale total score ≥ 21) and pre-training response inhibition deficits ( M  ≤ 75% successful inhibition on the Go/No-go) completed a 3-h, adaptive Go/No-go training designed to improve ability to withhold prepotent motor responses. Then forty-nine participants were randomized to an adaptive response inhibition training ( n  = 24, M  = 19.27 years, SD  = 0.70) or a waitlist condition ( n  = 25, M  = 18.31 years, SD  = 4.80). Behavioral response inhibition and self-reported trauma-related symptoms were assessed at pre- and post-training. Response inhibition training was associated with improved response inhibition on an untrained transfer Stop-Signal task and symptom reduction in PTSD compared to a waitlist group, at post-training. There was, however, reduced inhibition on a modified Go/No-go task from pre-to post-training. Overall, response inhibition deficits and PTSD symptoms are amenable to top-down remediation using response inhibition training. Our study provides preliminary evidence for the feasibility of response inhibition training in a PTSD sample characterized by response inhibition deficits. Highlights: Can individuals with PTSD and poor response inhibition improve with Go/No-Go training? Evaluated undergraduates with PTSD and Go/No-Go deficits in training vs. waitlist. Training improved Stop-Signal reaction time compared to a waitlist group from pre to post. Training worsened modified Go/No-Go accuracy compared to a waitlist group from pre to post. Training reduced PTSD severity compared to a waitlist group from pre to post trainings.